Unprofessional conduct by nurses: A document analysis of disciplinary decisions - Papinaho Oili; Häggman-Laitila Arja; Kangasniemi Mari (SAGE PUBLICATIONS LTD, 2022)
Background: A small minority of nurses are investigated when they fail to meet the required professional standards. Unprofessional conduct does not just affect the nurse but also patients, colleagues and managers. However, it has not been clearly defined.
Objective: The objective was to identify unprofessional conduct by registered nurses by examining disciplinary decisions by a national regulator.
Design: A retrospective document analysis.
Data and research context: Disciplinary decisions delivered to 204 registered nurses by the Finnish national regulatory authority from 2007 to 2016. The data were analysed with quantitative statistics.
Ethical consideration: The study received permission from the Finnish National Supervisory Authority for Welfare and Health and used confidential documents that were supplied on the basis of complete anonymity and confidentiality.
Findings: The mean age of the registered nurses who were disciplined was 44 years and 81% were female. Two-thirds had worked for their employer for 5 years or less, 53% had two or more employers and 18% had a criminal history. All the decisions included a primary reason for why the nurses were investigated, but there were also 479 coexisting reasons. In most cases, unprofessional conduct was connected to substance abuse (96%). In addition, stealing of medicine, a decreased ability to work and neglect of nursing guidelines were reported.
Discussion: We found that the nurses were investigated for unprofessional conduct for complex combinations of primary and coexisting reasons. Our study highlighted that more attention needs to be paid to the key markers for unprofessional conduct.
Conclusion: Unprofessional conduct is a complex phenomenon that is connected to nurses' individual and working backgrounds and has an impact on their work performance. More research is needed to identify how nursing communities can detect, manage and limit the serious effects and consequences of unprofessional conduct.